Something in between - De la Cruz, Melissa 1971- (Seventeen Fiction from Harlequin Teen, 2016)
Jasmine de los Santos has studied hard, made her Filipino immigrant parents proud and is ready to reap the rewards in the form of a full college scholarship to the school of her dreams. Then her parents reveal the truth: their visas expired years ago. Her entire family is illegal. That means no scholarships, maybe no college at all and the very real threat of deportation. Royce Blakely is funny, caring and spontaneous-- and the son of a congressman opposing an immigration bill. And now he's something else she may lose as her world comes apart.